Detection of Tetramethylsuccinonitrile in Food Packaging Containers of Plastics - Chakraborty, I.; P. Sharma, Gayn; Raghav, S.S.; Kapoor, B.L. (Asian Journal of Chemistry, 2010)
Tetramethylsuccinonitrile (TMSN) was determined in plastic products in contact with food. TMSN was extracted from plastic products with dichloromethane, steam distilled, extracted from the distillate with dichloromethane and determined with G.L.C. using nitrogen-phosphorus detector. TMSN was detected positive in 14 samples out of 35 samples. The resins in which TMSN was detected were polyacrylo nitrile (PAN), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA). The highest frequency of detection of TMSN was observed in PMMA (158 μg/g).